Apology strategies of Iranian ESL students / Haleh Parsa - Parsa, Haleh (2012)
The present study investigates native Persian-speaking ESL university students‟ apology strategies based on Cohen and Olshtain‟s (1981) frame work, including those which don‟t imply an apology to find out differences attributed to gender. The researcher has used an open questionnaire (Discourse Completion Test) as a controlled data elicitation technique to gather data. The sample of the study consists of one selected group of 40 Iranian postgraduate ESL students (20 males, 20 females) ranging between 24-35 from the Faculty of Languages and Linguistics and the Faculty of Education at University of Malaya. The findings indicate that Iranian male and female respondents used different percentages of apology and non-apology strategies. Unlike their male counterparts, Iranian females used more IFID and apology strategies to keep their successful relationships with the victim. Although both groups used non-apology strategies in their responses, male respondents applied different types of non-apology strategies to get rid of hard situation of apologizing. Considering significance levels, there were significantly more IFID strategies used by female respondents. While, in general, except for a few strategies, there is no statistically significant difference between the groups considering the number and type of apology and non-apology strategies used, which means, on the whole, gender does not play a significant role in the use of apology or non-apology strategies between male and female respondents.